Current salt reduction policies across gradients of inequality-adjusted human development in the WHO European region: minding the gaps - Rodriguez-Fernandez, R. (2014)
Objective: To assess current salty reduction policies in countries of the WHO European Region against the backdrop of varying levels of human development adjusted for income, education and health (longevity) inequalities. Design: Population-based, cross-sectional study, with data gathered through systematic review of relevant databases and supplementary information provided by WHO Nutrition Counterparts. Setting: Member States of the WHO European Region. Subjects: Inequality-adjusted Human Development Index scores were analysed against assessed levels of development and implementation of national nutrition policies and initiatives targeting population-level salt reduction. Results: Within the WHO European Region, Inequality-adjusted Human Development Index values among countries with no existing salt reduction initiatives (mean 0 .643 (SE 0.022)) were significantly lower than among those with either partially implemented/planned salt initiatives (mean 0.766 (SE 0.017), P<0.001) or fully implemented salt initiatives (mean 0.780 (SE 0.021), P<0.001). Conclusions: Where salt reduction strategies are implemented as an integral part of national policy, outcomes have been promising. However, low-and middle-income countries may face severe resource constraints that keep them from emulating more comprehensive strategies pursued in high-income countries. Care must be taken to ensure that gaps are not inadvertently widened by monitoring differential policy impacts of salt policies, particularly regarding trade flows.